2021
DOI: 10.1055/s-0041-1729745
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation, Patient Assessment, Anatomy, Pathophysiology, and Imaging of Pelvic Venous Disease

Abstract: Pelvic venous disorders (PeVDs) can result in several different clinical presentations, but can be challenging to distinguish from other etiologies of chronic pelvic pain (CPP). Clinical evaluation of CPP patients optimally should be performed in a multidisciplinary fashion and patients who may have PeVD should be referred for consultation with a vascular interventionalist whose evaluation would utilize an imaging workup to search for pelvic varices. Additionally, it is critical to quantify the quality-of-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…8,11 Pain from venous hypertension is thought to be related to activation of nociceptors from venous distention as well as endothelial dysfunction setting off an inflammatory response, which further potentiates valvular and endothelial dysfunction. 12,13 Estrogen and progesterone are thought to play a major role in the pathophysiology of pelvic venous insufficiency through their vasodilatory effects. [13][14][15] Pregnancy can precipitate and worsen existing pelvic venous disease due to the extreme physiologic levels of progesterone and estrogen in pregnancy combined with the mechanical venous outflow obstruction by the gravid uterus, and increased circulating blood volume, which may explain why patients can experience progression of symptoms with each pregnancy.…”
Section: Anatomy and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…8,11 Pain from venous hypertension is thought to be related to activation of nociceptors from venous distention as well as endothelial dysfunction setting off an inflammatory response, which further potentiates valvular and endothelial dysfunction. 12,13 Estrogen and progesterone are thought to play a major role in the pathophysiology of pelvic venous insufficiency through their vasodilatory effects. [13][14][15] Pregnancy can precipitate and worsen existing pelvic venous disease due to the extreme physiologic levels of progesterone and estrogen in pregnancy combined with the mechanical venous outflow obstruction by the gravid uterus, and increased circulating blood volume, which may explain why patients can experience progression of symptoms with each pregnancy.…”
Section: Anatomy and Pathophysiologymentioning
confidence: 99%
“…12,13 Estrogen and progesterone are thought to play a major role in the pathophysiology of pelvic venous insufficiency through their vasodilatory effects. [13][14][15] Pregnancy can precipitate and worsen existing pelvic venous disease due to the extreme physiologic levels of progesterone and estrogen in pregnancy combined with the mechanical venous outflow obstruction by the gravid uterus, and increased circulating blood volume, which may explain why patients can experience progression of symptoms with each pregnancy. [16][17][18] Central sensitization, a neurobiological phenomenon of abnormal pain processing that can result in amplification of pain signals which can spread to adjacent organs, is also thought to contribute to the pain associated with pelvic venous disease, and offers an explanation of how the severity of pelvic venous insufficiency does not correlate with severity of symptoms.…”
Section: Anatomy and Pathophysiologymentioning
confidence: 99%
“…Data supporting factors that should be treated are lacking, but studies have reported that findings associated with inclination to treat were pelvic contrast retention of more than 20 seconds, gonadal vein diameter of 6 mm or more, reflux into the iliac vein, or contrast flow via escape points into perineal, labial, or lower extremity varicosities. 21…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…The origin of pelvic pain can be found in more than just the dilation and the related nociceptor activation [5].…”
Section: Introductionmentioning
confidence: 99%